REPRESENTASI DIKTATOR DALAM FILM THE INTERVIEW (STUDI SEMIOTIKA ROLAND BARTHES) - Fandy Sandra Rahmadhani; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
There are Stories in the film that illustrates how A leader of North Korea who is an authoritarian, cruel dictator who oppresses his people to achieve his will. The phenomenon that occurred in this study shows about the assassination attempt against the North Korean president utilizing a TalkShow show to dismantle the ugliness of the North Korean government. This study aims to determine the meaning of dictators based on semiotics analysis Roland Barthes and dictator representation in the movie "The Interview".This research use method qualitative, with approach of analysis of semiotica Roland Barthes, focussed subjek to president of North Korean as a dictator seen through Denotation facet ( signifier) explain relation of penanda and of petanda at reality, yielding meaning of eksplisit. Konotasi ( signified) explain relation of penanda and of petanda at non reality, yielding meaning of implisit Myth and ( myth) explain trust and habit going into effect in society. Sequence divided to become 3 part ranging the start of the first sequence or the introduction round, or round confrontation sequence 2, sequence 3 or resolution.Data collecting by determining korpus which there are in the film as according to kategorisasi which have been determined.Result of from this research indicate that representasion of dictator in The Interview movie . First, the dictator denotation in The Interview movie is a dictator who has a rude leadership style and has a cruel nature in addressing the problem. Second, the dictator's connotation in The Interview movie serves as a dictator who has the opposite nature of dictators in general. Third, the myths depicted in the figure of a dictator in Tthe Interview movie is a figure who likes to collect glamorous objects despite the country he leads the economic and food crisis. Fourth, the dictatorial representation in The Interview movie presents the opposite side of the commonly known in terms of character or nature so that the film is satire that is not expressed directly against the dictatorial rule of Kim Jong Un.Keywords: The Interview, Semiotica Roland Barthes, Dictator, Kim Jong Un